Math

Log2 (x-6) + log2 (x-4) - log2 X=2

  1. 👍 0
  2. 👎 0
  3. 👁 346
  1. [(x - 6)(x - 4)] / x = 4 ... x^2 - 10 x + 24 = 4 x ... x^2 - 14 x + 24 = 0

    (x - 12) (x - 2) = 0

    x = 12 , x = 2

    logs are not defined for negative values ... x = 12

    1. 👍 1
    2. 👎 1
  2. The answer is 8

    1. 👍 0
    2. 👎 1

Respond to this Question

First Name

Your Response

Similar Questions

  1. Algebra

    expand log2 (8x^2+48X+72)

  2. Math

    I am lost!! Find the inverse function of f(x)=log2(4x) Thanks

  3. precalc

    Solve the logarithmic equation for x. (Enter your answers as a comma-separated list.) log2(x + 17) − log2(x − 2) = 1 2 is the base for the log.

  4. Mathematics

    Solve for x if I: Log2(x²-2x+5)=2 ii: Log 3(x²+2x+2)=0

  1. Mathematics

    Find x such that log3(2x-1)=1+log2(x+1)?

  2. trig

    solve for x log4 64+ log2 2 ________________ =x log3 81

  3. Discrete Mathematics

    If f(x) = log2 (x - 2)3 and g(x) = log8 (x - 2), when is (f + g)(x) = 0?

  4. math

    express log2+log3 as a single logarithm

  1. math/algebra

    solve the equation log2(3x-2) - log2 (x-5)=4

  2. pre cal

    f(x)= log2 (x-1).The vertical asymptote of the function f(x) has equation:?

  3. Math - Logarithmic

    Solve: 2^(5x-6) = 7 My work: log^(5x-6) = log7 5x - 6(log2) = log7 5x = log7 + 6(log2) x = (log7 + log2^6) / 5 And textbook answer: (log7) / (log2) What did I do wrong?

  4. add maths

    Given that log2 3=h and log2 5=k, express log2 0.45 in terms of h and k.

You can view more similar questions or ask a new question.